DNA microbeads for spatio-temporally controlled morphogen release within organoids [research data] - Walther, Tobias; Afting, Cassian; Drozdowski, Oliver; Schlagheck, Christina; Schwarz, Ulrich S.; Wittbrodt, Joachim; Göpfrich, Kerstin (Universität, 2024)
Organoids have proven to be powerful in vitro model systems that mimic features of the corresponding tissue in vivo. However, across tissue types and species, organoids still often fail to reach full maturity and function because biochemical cues cannot be provided from within the organoid to guide their development. The establishment of such tools has been identified as a major goal of the field. Here, we introduce DNA microbeads as a novel tool for implementing spatio-temporally controlled morphogen gradients inside of organoids at any point in their life cycle. The DNA microbeads are formed in a simple one-pot process, they can be stored for a year and their stiffness and surface modification is tunable to mimic the corresponding tissue. Employing medaka retinal organoids and early embryos, we show that DNA microbeads can be integrated into embryos and organoids by microinjection and erased in a non-invasive manner with light. Coupling a recombinant surrogate Wnt to the DNA microbeads, we demonstrate the spatio-temporally controlled release of the morphogen from the microinjection site, which leads to morphogen gradients resulting in the formation of retinal pigmented epithelium (RPE) while maintaining retinal ganglion cells. The spatial localization of the induced RPE was shown to directly correlate with the DNA microbeads’ position. We were thus able to bioengineer retinal organoids to more closely mirror the cell type diversity of in vivo retinae. The DNA microbead technology can easily be adapted to other organoid applications for improved tissue mimicry.
Gefördert durch: Deutsche Forschungs Gemeinschaft (DFG): EXC-2082/1 - 390761711; European Research Council (ERC): ENSYNC (No. 101076997)
Gesehen am 18.09.2024
Keywords: Forschungsdaten; Datenbank